ANALISIS PENGARUH TINGKAT HUNIAN HOTEL, JUMLAH WISATAWAN DAN JUMLAH OBJEK WISATA TERHADAP PENDAPATAN SEKTOR PARIWISATA DI KABUPATEN KEBUMEN - Muhammad Ihsan Alwi; Hadi Sasana; Gentur Jalunggono (Universitas Tidar, 2020)
This study aims to analyze the effect of hotel occupancy rates, number of tourists, and thenumber of tourist objects on the income of the tourism sector in Kebumen Regency from 19902017. The dependent variable is tourism sector income and the independent variable is hotel occupancy rate, number of tourists, and number of tourist objects. The data used in the form ofsecondary data with the form of time series data obtained from the Central Statistics Agency (BPS) of Kebumen Regency and Central Java Province, the Department of Youth, Sports and Tourism, Kebumen Regency and Central Java Province. The method of data analysis uses Multiple Linear Regression Analysis. The results of the analysis show that the variable number of tourists does not significantly influence the income of the tourism sector in Kebumen Regency, the variable occupancy rate of hotels and the number of tourist objects significantly influence the income of the tourism sector in Kebumen Regency, there are simultaneous or joint effects and significance of the level variable hotel occupancy, number of tourists and number of tourist objects to the income variable of the tourism sector in Kebumen Regency.